2007
DOI: 10.1172/jci32282
|View full text |Cite
|
Sign up to set email alerts
|

Normal human dermis contains distinct populations of CD11c+BDCA-1+ dendritic cells and CD163+FXIIIA+ macrophages

Abstract: We used a panel of monoclonal antibodies to characterize DCs in the dermis of normal human skin. Staining for the CD11c integrin, which is abundant on many kinds of DCs, revealed cells in the upper dermis. These cells were positive for blood DC antigen-1 (BDCA-1; also known as CD1c), HLA-DR, and CD45, markers that are also expressed by circulating myeloid DCs. A small subset of CD11c + dermal cells expressed DEC-205/ CD205 and DC-lysosomal-associated membrane glycoprotein/CD208 (DC-LAMP/CD208), suggesting some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
317
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(351 citation statements)
references
References 34 publications
30
317
1
3
Order By: Relevance
“…Several populations of DCs take up residence in different tissues and carry common as well as unique biological functions (2,3). The healthy human skin displays at least three DC populationsLangerhans cells (LCs) in the epidermis and interstitial CD1a + and CD14 + DCs in the dermis (4,5). Each of the different skin DC subsets carries out specialized functions.…”
Section: Endritic Cells (Dcs) Are Potent Antigen-presenting Cells (mentioning
confidence: 99%
“…Several populations of DCs take up residence in different tissues and carry common as well as unique biological functions (2,3). The healthy human skin displays at least three DC populationsLangerhans cells (LCs) in the epidermis and interstitial CD1a + and CD14 + DCs in the dermis (4,5). Each of the different skin DC subsets carries out specialized functions.…”
Section: Endritic Cells (Dcs) Are Potent Antigen-presenting Cells (mentioning
confidence: 99%
“…FXIII-A is also expressed in some subpopulations of dendritic cells (DCs) such as migratory dermal DCs (Nestle et al, 1993), DC-like cells derived from CD34+ progenitor cells (Caux et al, 1996), a subset of dermal cells termed ¨dermal dendrocytes¨ (Cerio et al, 1989;Quatresooz et al, 2008), and in vitro monocyte-derived DCs (Grassi et al, 1998). It has also been recently identified in a population of dermal cells with a marked plasticity between tissue-resident DCs and macrophages (Zaba et al, 2007), suggesting that FXIII-A expression may associate to an alternative cellular activation state following the stimulation of DCs and macrophages by IL-4 (Nestle and Nickoloff, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Whether such macrophage populations exist in human and are capable of Ag-presenting function remains to be confirmed. In another recent study, normal human dermis has been shown to contain immunostimulatory dendritic cells marked by CD11c and BDCA-1 while the macrophage population identified by CD163 and factor XIIIA showed much less immunostimulatory potency (23).…”
Section: Professional Apcs Are the First Immune-sensitive Depots For mentioning
confidence: 93%